Early Serum Gut Hormone Concentrations Associated With Time to Full Enteral Feedings in Preterm Infants. Issue 1 (July 2018) - Shanahan, Kristen H.; Yu, Xinting; Miller, Laura G.; Freedman, Steven D.; Martin, Camilia R.
ABSTRACT: Objectives: The primary objective of this study was to evaluate early postnatal serum gut hormone concentrations in preterm infants as predictors of time to full enteral feedings. The secondary objective was to identify infant characteristics and nutritional factors that modulate serum gut hormone concentrations and time to full enteral feedings. Methods: Sixty-four preterm infants less than 30 weeks of gestation were included in this retrospective cohort study. Serum gut hormone concentrations at postnatal days 0 and 7 were measured using enzyme-linked immunosorbent assays. Linear regression and mediation analyses were performed. Results: Median (interquartile range) serum concentrations of glucose-dependent insulinotropic peptide (GIP) and peptide YY (PYY) on postnatal day 7 were 31.3 pg/mL (18.2, 52.3) and 1181.7 pg/mL (859.0, 1650.2), respectively. GIP and PYY concentrations on day 7 were associated with days to full enteral feedings after adjustment for confounders (β = −1.1, P = 0.03; and β = −0.002, P = 0.02, respectively). Nutritional intake was correlated with serum concentrations of GIP and PYY on postnatal day 7 and time to full enteral feedings. Mediation analysis revealed that the effect of serum gut hormone concentrations on time to full enteral feedings was not fully explained by nutritional intake. Intrauterine growth restriction, mechanical ventilation on postnatal day 7, and patent ductus arteriosus treated with indomethacin were associated with longer time to full enteral feedings. Conclusions: Serum concentrations of GIP and PYY on postnatal 7 are independently associated with time to full enteral feedings. The link between serum gut hormone concentrations and time to full enteral feedings is not fully mediated by nutritional factors, suggesting an independent mechanism underlying the influence of gut hormones on feeding tolerance and time to full enteral feedings. Abstract : Supplemental Digital Content is available in the text